Investigating and Exploiting the Antibacterial Potential of Clove Eugenia caryophyllyum Extracts while Utilizing it to the Maximum to Develop Liquid Soap against Drug Resistant Bacteria Causing Skin Diseases - Kaur, Manpreet (International Journal of Pharmaceutical & Biological Archive, 2015)
Investigating and Exploiting the Antibacterial Potential of Clove Eugenia caryophyllyum Extracts while Utilizing it to the Maximum to Develop Liquid Soap against Drug Resistant Bacteria Causing Skin Diseases Investigating and Exploiting the Antibacterial Potential of Clove Eugenia caryophyllyum Extracts while Utilizing it to the Maximum to Develop Liquid Soap against Drug Resistant Bacteria Causing Skin Diseases Investigating and Exploiting the Antibacterial Potential of Clove Eugenia caryophyllyum Extracts while Utilizing it to the Maximum to Develop Liquid Soap against Drug Resistant Bacteria Causing Skin Diseases Investigating and Exploiting the Antibacterial Potential of Clove Eugenia caryophyllyum Extracts while Utilizing it to the Maximum to Develop Liquid Soap against Drug Resistant Bacteria Causing Skin Diseases